2013
DOI: 10.3346/jkms.2013.28.6.888
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden and Epidemiology of Pneumonia in Korean Adults Aged over 50 Years

Abstract: This study was performed to estimate the direct medical costs and epidemiology of pneumonia in adults of Korea. We conducted a multi-center, retrospective, observational study and collected data targeting for community-acquired pneumonia patients ( ≥ 50 yr) from 11 hospitals. Costs attributable to the treatment of pneumonia were estimated by reviewing resource utilization and epidemiology data (distribution of pathogen, hospital length of stay, overall outcome) were also collected. A total 693 patients were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 18 publications
1
36
2
Order By: Relevance
“…A Korean study of the pneumonia burden in 764 inpatients with CAP (age, ≥ 50 years) revealed that 3.2% patients died during treatment [10]. Mortality occurs primarily in the elderly and is frequently associated with underlying diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A Korean study of the pneumonia burden in 764 inpatients with CAP (age, ≥ 50 years) revealed that 3.2% patients died during treatment [10]. Mortality occurs primarily in the elderly and is frequently associated with underlying diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, to preserve the credibility of the data, as well as to reflect the reality of the local situation, we adopted the efficacy data of PCV13 from a verified large-scale, double-blind, randomized, placebo-controlled research (CAPiTA). 46 In addition, epidemiological and cost data on pneumococcal diseases were taken from existing local sources, 7,8,10,[48][49][50] as completely as possible. Lastly, the risk group ratio reflected in this study (Supplementary Table 1) is considered to be lower than what is usually estimated by expert groups in reality.…”
Section: Discussionmentioning
confidence: 99%
“…6 In Korean adults, the annual incidence rates of community-acquired pneumonia (CAP) range from 538 to 707 cases per 100,000 persons, which increases with age. 7 Among CAP cases, S. pneumoniae accounts for 21.1-43.6%, [8][9][10][11][12][13][14][15][16][17][18] and 5.9% of the cases result in death. 10 The average per-capita medical fee was reported at 1,887 USD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations